The modernist bestiary : translating animals and the arts through Guillaume Apollinaire, Raoul Dufy and Graham Sutherland /: translating animals and the arts through Guillaume Apollinaire, Raoul Dufy and Graham Sutherland. (2020) - Unknown
No abstract available